Enhanced visible light driven Photocatalytic activity of MnO2 nanomaterials and their hybrid structure with carbon nanotubes. (28th October 2020) - Warsi, Muhammad Farooq; Bilal, Muhammad; Zulfiqar, Sonia; Khalid, Muhammad Usman; Agboola, Philips O; Shakir, Imran
Abstract: MnO2 nanomaterials were synthesized using a simple wet redox method. Crystal structure of as prepared pure and Al doped MnO2 nanomaterials was investigated using X-ray diffraction (XRD) technique. Crystal structure was further confirmed by FTIR analysis. Morphology of pure MnO2, Al doped MnO2, MnO2 /CNT hybrid structure and Al doped MnO2 /CNT hybrid structure was studied using scanning electron microscopy (SEM). Energy dispersive X-ray spectroscopy confirmed the presence of all the constituent atoms in the crystal structure of all the samples. Bandgap value was found to decrease with the modification (doping and hybrid structure). Photocatalytic efficiency of all the MnO2 samples was studied using the photodegradation of methylene blue (MB) under the visible light (solar radiation). Effect of different intermediates on the photodegradation efficiency was studied using different scavengers.